PEMANFAATAAN MEDIA MULBA DALAM MENINGKATKAN LITERASI PADA SISWA KELAS II DI SDK JOGE (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to describe the use of multilingual media in improving literacy in class II students of SDK Joge. This type of research is qualitative descriptive research. The subjects of this study were 16 class II students of SDK Joge. The data collection methods used in this study were observation, interview and documentation methods. The data in this study were analyzed using Milles and Huberman data analysis techniques consisting of 1) data collection, 2) data reduction, 3) data presentation and 4) drawing conclusions. The results of this study indicate that after the multilingual media, students experienced an increase in vocabulary use, an increase in communication, an increase in writing skills, an increase in learning interest, an increase in student confidence in learning and strengthening student memory. Thus, it can be concluded that through student activities observing multilingual learning media, students re-observing the contents of the multilingual media that they have observed and word-composing activities can improve literacy in class II students at SDK Joge.